Arrest on Reasonable Suspicion and Credible Information: Policy and Practice in Bangladesh - Bari, Hussain Mohmmad Fazlul (Kathmandu School of Law Review, 2017)
In Bangladesh, a police officer has the discretion to arrest an individual on the pretext of “reasonable suspicion” and “credible information" even without a warrant of arrest from the Magistrate. Though there are statutory and constitutional safeguards to protect liberty, security and human rights of the arrestee, practically there are numerous allegations of misuse or abuse of Section 54 of Code of Criminal Procedure 1898 by the police officers. High Court Division (HCD) in ‘BLAST HCD case’ and ‘Saifuzzaman Case’ rightly denounced all sorts of such abuses. HCD held that some provisions were, to some extent, inconsistent with the Constitution and also recommended for amendment of those questionable provisions. HCD also provided some directives to be followed while applying those existing provisions for arrest until such laws are modified. However, after rigorous hearing for about 12 years, Appellate Division (AD) dismissed the appeal preferred against BLAST HCD judgment. While AD concurred with the observations and findings of the HCD, it found recommendations and directives of the HCD as being either redundant or an exaggeration. In view of the observations of the AD, the legislature should also make a holistic review of Code of Criminal Procedure.